Role of prostaglandins and specific place in therapy of bimatoprost in the treatment of elevated intraocular pressure and ocular hypertension: A closer look at the agonist properties of bimatoprost and the prostamides - Scott D Smid (Dove Medical Press, 2009)
Scott D SmidDiscipline of Pharmacology, School of Medical Sciences, Faculty of Health Sciences, University of Adelaide, Adelaide, SA, AustraliaAbstract: Bimatoprost is the only representative of a novel class of prostaglandin ethanolamide (prostamide) compounds used therapeutically as an efficacious treatment for glaucoma. The pathways through which bimatoprost works to improve uveoscleral outflow to relieve elevated intraocular pressure are similar to those of the conventional prostaglandins used in glaucoma therapy, with some evidence of a preferential action at the trabecular meshwork. The pharmacology of bimatoprost is however, unclear. Pharmacological evidence supports a specific and distinct receptor-mediated agonist activity of bimatoprost at ‘prostamide’ receptors, which is selective to the prostamides as a class. However, other studies have reported either activity of bimatoprost at additional prostanoid and nonprostanoid receptors, or a conversion of bimatoprost to metabolites with agonist activity at prostaglandin FP receptors in the human eye. The formation of endogenous prostamides has been demonstrated in vivo, by a novel pathway involving the cyclooxygenase-2-mediated conversion of endogenous cannabinoid (endocannabinoid) substrates. Irrespective of the pharmacology of bimatoprost and the prostamides in general, further studies are needed to determine the biological role and biochemical pathology of prostamides in the human eye, particularly in glaucoma. Such studies may improve our understanding of uveoscleral flow and may offer new treatments for controlling intraocular pressure.Keywords: bimatoprost, endocannabinoid, glaucoma, prostamides, trabecular meshwork